THE INFLUENCE OF ORGANIZATIONAL COMMITMENT, WORK DISCIPLINE AND MOTIVATION TO HOTEL EMPLOYEE PERFORMANCE IN BOGOR CITY - Wasiman, Wasiman (EDUTECH CONSULTANT, 2017)
This study aims to determine the influence of organizational commitment, discipline and motivation on employee performance at the Hotel in Bogor. This study uses questionnaires data distributed to four-star hotel employees in the city of Bogor by distributing questionnaires 250 respondents with levels of respondents ranging from managers to supervisors. This study uses the level of individual analysis. The object of research is four-star hotel employees in Bogor City. This research uses multiple sterile linear regression test which includes validity, reliability, normality, and r square test. The result showed that the coefficient of determination (R2) has a value of 0.734 which means that the variable of employee performance variable can be explained by organizational commitment variable, discipline and motivation, that is 73, 4.0%, while the rest is 26, 6% are influenced by factors not present in this study.